Perbandingan Penggunaan SAW dan AHP untuk Penentuan Prioritas Maintenance Rusunawa Depok - Aditya Alif; Ilham Rahmaditia Arlingga; Ika Nur Suciati; Bagus Priambodo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Low costing flats are subsidized by the local government, but until now, there are still many flats that do not have a good system to manage the facility. The obstacle faced by the current management is that there is no system that can give priority scale there is no system that can provide a fast and precise priority scale to determine facilities that need to be repaired immediately by the management based on the availability resource so fast which facilities need to be repaired as soon as possible. Such as determining the priority of repairs among damaged public toilets or repairing damaged garden chairs. In this study, we propose the Simple Additive Weighting (SAW) method to determine priority maintenance for facilities in low-cost flats. The results of calculations using SAW are evaluated by comparing the results of calculations using the Analytical Hierarchy Process (AHP). The experimental results show that the ranking results using the SAW method are better than the results of ranking using the AHP, furthermore using SAW is also more efficient because the complexity required in the calculation is simpler.